2000
DOI: 10.1142/s0192415x00000477
|View full text |Cite
|
Sign up to set email alerts
|

Five Cases of MRSA-Infected Patients with Cerebrovascular Disorder and in a Bedridden Condition, for Whom Bu-Zhong-Yi-Qi-Tang (Hochu-ekki-to) Was Useful

Abstract: The herbal formula bu-zhong-yi-qi-tang (hochu-ekki-to, 5 grams per day) was administered to five MRSA-infected bedridden patients with cerebrovascular disorder, dementia and, in two cases, bed sores, who had resistance to several antibacterial drugs. After hochu-ekki-to the patients showed an excellent result; disappearance of MRSA, improvement of their general condition, and no side effects. Therefore, it is thought that hochu-ekki-to may be a useful drug for MRSA-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Several studies of HET on microbial infections have been investigated. In a small-scale clinical trial about MRSA infection, eradication of MRSA was successful when HET was administered to five MRSA carriers’ patients [ 12 ]. Another study showed that when HET was administered to 34 asymptomatic patients from which MRSA was isolated from urine, MRSA was not isolated from urine in 12 patients, and 10 patients decreased the bacterial volume to less than 1/100 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of HET on microbial infections have been investigated. In a small-scale clinical trial about MRSA infection, eradication of MRSA was successful when HET was administered to five MRSA carriers’ patients [ 12 ]. Another study showed that when HET was administered to 34 asymptomatic patients from which MRSA was isolated from urine, MRSA was not isolated from urine in 12 patients, and 10 patients decreased the bacterial volume to less than 1/100 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hochuekkito extract (HET) has been used to treat severe infirmity such as weakness and loss of appetite of the elderly [ 11 ]. As HET is a popular alternative medicine in Japan, limited scientific evidence is available on the use of HET for the treatment of MRSA colonization [ 12 , 13 ]. Thus, the clarification of the precise mechanism of Hochuekkito efficacy against MRSA colonization has been desired.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of skin diseases, few clinical studies have reported on the efficacy of HET. In these studies, HET is reportedly effective for methicillin‐resistant Staphylococcus aureus skin infection and atopic dermatitis …”
Section: Introductionmentioning
confidence: 99%
“…In these studies, HET is reportedly effective for methicillin-resistant Staphylococcus aureus skin infection and atopic dermatitis. 29,30 To date, there has been no clinical study on the relationship between HET and wound healing. We hypothesized that HET as an adjunctive therapy would be useful for promoting the healing of chronic wounds, as wounds are microecological environments filled with large amounts of diverse and often virulent microbes.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental animal models, orally administered HOT was protective against several microbes, including Listeria monocytogenes [4,5], Helicobacter pylori [6], influenza virus [7], candida [8], and cytomegalovirus [9]. In human study, HOT was reported to be effective against MRSA infection [10]. Mice administered HOT showed enhanced production of IFN-g by CD4+ T cells and antigen-presenting capacity by tissue macrophages in experimental L. monocytogenes infection [5].…”
Section: Introductionmentioning
confidence: 99%